Use of Non-Verbal Representations to Define Concept of Pulse Conditions in Traditional Chinese Medicine Standards - Chun-Ke Zhang; Yi-Qin Wang; Rui Guo; Hai-Xia Yan; Jian-Jun Yan; Wen-Jie Wu; Jing Li; Su Lin (Chinese Medicine and Culture)
Abstract. The standardization of terms and definitions is fundamental to all activities in the domain of traditional Chinese medicine (TCM). For decades, definitions of TCM terminology relied on conventional verbal representations to differentiate between related concepts. However, the ancient Chinese is obscure and comprises a massive volume of information, making it difficult to convey the definition accurately in other languages. This article proposes a potential solution that the definition for pulse terminology can be supplemented by modern means of non-verbal representation, i.e., using pulse waveform graphs and parameters to complete the definition of each pulse. A discussion of the challenges of obtaining reliable data is also included.